The Change of Catalase Enzyme Activity in Soils by The Land Use - Kravkaz Kuşçu, İnci Sevinç; Karaöz, Mustafa Ömer (Turkish Science and Technology Publishing (TURSTEP), 2021)
Analysing the factors driving the population size and activities of soil microorganisms is important for understanding the soil ecosystem‘s structure and functioning. For this purpose, the soil enzymes are used as an indicator of soil microbial activity and soil fertility. Although there are many studies on the distribution and activities of various soil enzymes in soils under monoculture or crop alternation conditions, there are only few studies examining the ecological relationship in natural ecosystems, especially by using enzymes. In this study, it was aimed to determine the effect of different land uses on the catalase enzyme activity in soil. For this purpose, the catalase enzyme activities in soil samples taken from 0-5cm and 5-10cm depths in agricultural, forest, and pasture lands in north and south exposures were determined and the effects of different land use, exposure, and soil depth conditions on the enzyme activities were investigated. At the end of the study, it was determined that the catalase enzyme activity significantly differed by the land use and the highest level of catalase enzyme activity in both south and north exposures and at both depth levels was found in forest soils, whereas the lowest level of activity was found in agricultural lands in north exposure and pasture soils in south exposure.
Keywords: enzyme; exposure; S; Agriculture (General); catalase; soil depth; land use; Agriculture; S1-972; 2. Zero hunger; 15. Life on land